Anti-Trypanosomal Activity and Cytotoxicity of Some Compounds and Extracts from Nigerian Medicinal Plants - Igoli, John O.; Gray, Alexander I.; Clements, Carol J.; Mouad, Hazar A. (IntechOpen, 2011)
None